Interfacial Protection Engineering of Sodium Nanoparticles toward Dendrite‐Free and Long‐Life Sodium Metal Battery. Issue 35 (26th July 2021) - You, Shunzhang; Ye, Minghui; Xiong, Jiaming; Hu, Zuyang; Zhang, Yufei; Yang, Yang; Li, Cheng Chao
Abstract: The instability of interfacial solid‐electrolyte interphase (SEI) layer of metallic sodium (Na) anode during cycles results in the rapid capacity decay of sodium metal batteries (SMBs). Herein, the concept of interfacial protection engineering of Na nanoparticles (Na‐NPs) is proposed first to achieve stable, dendrite‐free, and long‐life SMB. Employing an ion‐exchange strategy, conformal Sn‐Na alloy‐SEI on the interface of Na‐NPs is constructed, forming Sn@Na‐NPs. The stable alloy‐based SEI layer possesses the following three advantages: 1) significantly enhancing the transport dynamics of Na + ions and electrons; 2) enabling the well‐distributed deposition of Na + ions to avoid the growth of dendrites; and 3) protecting the Sn@Na‐NPs anode from the attack of electrolyte, thereby reducing the parasitic reaction and boosting the Coulombic efficiency of SMBs. Because of these virtues, the symmetric Sn@Na‐NPs cell shows an ultralow voltage hysteresis of 0.54 V at 10 mA cm −2 after 600 h. Paired with the Na3 V2 (PO4 )2 O2 F (NaVPF) cathode, the NaVPF‐Sn@Na‐NPs full cell exhibits an initial discharge capacity of 89.2 mAh g −1 at 1 C and a high capacity retention of 81.6% after 600 cycles. Abstract : The conformal Sn‐Na alloy interfacial layer on the surface of Sn@Na‐nanoparticles anode is able to effectively protect it from the attack of solvent, enabling the dendrite‐free Na plating/stripping and achieving stable long‐term cycling stability in both symmetric cell and sodium metal full batteries.